Analysis of Entrepreneurship Education and Creativity on Technopreneurship Readiness, Mediated by Technopreneurship Intention in Vocational Schools Majoring in Information Technology - Shofiyatul Hidayah; Agus Wibowo; Suparno (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study investigates the effect of entrepreneurship education and creativity on technopreneurship readiness, mediated by technopreneurship intention, among vocational high school students in information technology. Using a quantitative approach, data were collected from 115 respondents out of a total population of 162 students at SMKN 45 and SMKN 53 Jakarta. Structural Equation Modelling–Partial Least Squares (SEM-PLS) version 4.0.2 was employed for hypothesis testing. The results show that both entrepreneurship education and creativity have positive and significant effects on technopreneurship intention, and together they positively and significantly influence technopreneurship readiness through technopreneurship intention. These findings highlight the critical role of entrepreneurship education, creativity, and technopreneurship intention in strengthening technopreneurship readiness among vocational high school students in the information technology field.